Mucosal washes are useful for sampling intestinal mucus-associated microbiota despite low biomass - Jennifer N. Martinez-Medina; Fereshteh Ghazisaeedi; Catharina Kramer; Jörn F Ziegler; Victoria McParland; Paul W. Mönch; Britta Siegmund; Víctor Hugo Jarquín-Díaz; Marcus Fulde; Sofia K. Forslund-Startceva (Gut Microbes)
Understanding the dynamic relationship between mucus-associated microbiota and host health is critical. However, studies predominantly using stool samples may not accurately represent these bacterial communities. Here, we investigated the mucus-associated microbiota in the gastrointestinal tract of mice and the terminal ileum of humans using different sample types: mucosal washes, brushes, scrapings, and intestinal contents in mice and biopsies, brushes and mucosal washes in humans. We used DNA quantification and 16S rRNA amplicon sequencing to evaluate the comparability of the information yielded from the different sample types under a controlled benchmark. In mice, mucosal washes and brushes had comparative bacterial DNA and host DNA contamination than scraping samples. Similarly, in humans, washes outperformed biopsies in bacterial DNA content. Read counts and microbiota alpha diversity remained remarkably similar in mice and between brushes and washes in humans. The composition of the microbiota varied based on the subsegment and sample type in mice and sample type in humans. We conclude that washes and brushes reduce host contamination without inducing substantial compositional bias when sampling mucosal microbiota. Our findings suggest that mucosal washes and brushes are a viable alternative to biopsies in humans and scrapings in mice, thereby improving the transferability of results across hosts. Our study highlights the importance of focusing on mucus-associated microbiota to better capture host–microbiome interactions at their closer interface.